MRI Findings and Prediction of Time to Progression of Patients with Hepatocellular Carcinoma Treated with Drug-eluting Bead Transcatheter Arterial Chemoembolization - Lee, Seungsoo; Kim, Kyung Ah; Park, Mi-Suk; Choi, Sun Young (Journal of Korean medical science, 2015)
The purpose of this study was to investigate the utility of MRI findings after drug-eluting beads (DEB) - transcatheter arterial chemoembolization (TACE) for hepatocellular carcinoma in predicting time to progression (TTP). This study included 48 patients with 60 lesions who underwent liver MRI within 3 months after DEB-TACE. MRI was assessed for arterial enhancement pattern, late washout, arterioportal shunt, signal intensity on T2-weighted image, intratumoral septa, enhancing tissue on subtraction images, and treatment response. Cox-regression analysis was performed to identify independent factors to predict TTP. TTP was calculated using the Kaplan-Meier method with the log-rank test. Per lesion, 30 achieved complete remission, 22 had a partial response, and the remaining 8 lesions displayed stable disease on MRI. Arterial enhancement pattern, washout and enhancing tissue on subtraction images from MRI were associated with viable tumor on the last follow-up computerized tomography. Arterial enhancement, washout and enhancing tissue on subtraction images were significant predictors of TTP, but only enhancing tissue on subtraction images remained a significant predictor of TTP (P=0.018) in the multivariate analysis. TTP was longer in the group without enhancing tissue on subtraction images compared to the group with enhancing tissue (601 days vs. 287 days, P<0.001). Enhancing tissue on subtraction images from MRI after DEB-TACE is predictive for longer TTP.